Analisis Feminisme Liberal pada Antologi Cerpen Perempuan dan Perempuan Karya Bagus Satria - Jumaroh Ristian Ningsih; Retno Wulandari; Cintya Nurika Irma (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
The purpose of this study is to describe, analyze, and examine the feminism contained in the anthology of the short story "Perempuan dan Perempuan" by Bagus Satria. The data source for this research is the short story Anthology of ”Perempuan dan Perempuan” by Bagus Satria. The method used in this study is a qualitative descriptive method. The research data is liberal feminism in the anthology of the short story “Perempuan dan Perempuan” by Bagus Satria. The type of research used in this research is qualitative research with descriptive methods. The data used are texts related to aspects of feminism in the short story Anthology of ”Perempuan dan Perempuan”. Data analysis techniques (1) read the entire contents of the short story, (2) mark and record the quotations on the short story, (3) classify the findings, (4) analyze the findings according to the research problem, (5) the last step is concluded. The results of the research show that there is feminism in the short story “Perempuan dan Perempuan” by Bagus Satria.